Special Issue “Model Predictive Control: Algorithms and Applications”: Foreword by the Guest Editor - Ławryńczuk, Maciej (Algorithms, 2022)
Model Predictive Control (MPC) is an advanced control method that makes it possible to effectively control Multiple-Input Multiple-Output (MIMO) processes subject to different types of constraints [...]